Penerapan Model Pembelajaran Picture and Picture Pada Mata Pelajaran PPKn Sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik di Kelas IV SD Negeri Lingketeng Kecamatan Lobu Kabupaten Banggai - Nurhasanah Nurhasanah*; Mukhlish A. Laadi; Jamil Sulaya; Abd. Rahman; Zulhidja Tumbingo (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the application of the Picture and Picture Learning Model in PPKn subjects as an Effort to Improve Student Learning Outcomes in Class IV SD Lingketeng, Lobu District, Banggai Regency. This type of research is Classroom Action Research (CAR). The subjects of this study were the fourth grade students of SD Negeri Lingketeng, which consisted of 20 students. The study carried out 2 cycles of data collection in this study used the Learning Outcomes test in the form of multiple choice totaling 12 item numbers, teacher observation sheets in managing learning through the application of the Picture and Picture Learning Model and observing students' activities in learning through the Picture and Picture Model. Based on the results of data analysis, it shows that there has been an increase in the learning activities of students and teachers as well as the level of student learning outcomes. Based on the results of data analysis it is known that individually learning outcomes have increased and the acquisition of an average value of learning outcomes in cycle I: achieving an average student activity is obtained 60%, teacher activity with an average achievement of 68.1% in cycle II achieves participant activity student average achievement 86%, teacher activity average achievement 96%. The score for the class average of the first cycle learning outcomes test was 77% with good criteria and the second cycle was 86% with very good criteria. Thus it can be concluded that the Application of the Picture and Picture Learning Model can improve the learning outcomes of PPKn Theme 1 The Beauty of Togetherness of class IV SD Negeri Lingketeng, Lobu District, Banggai Regency.